Techniczna konstrukcja/odkrywanie prawd (1): odkrycie Talesa i miary średniowieczne - Chwałczyk, Franciszek (Humaniora. Czasopismo Internetowe, 2019)
Writing about the relationship between Martin Heidegger’s philosophy and Marxist philosophy, Jean Beaufret states (after Hegel) that it was in Descartes philospohy that the very essence of truth was resolved in a new way. I interpret it as follows: it is not statement mainly about the fact that its content – what is considered to be true – has changed. This has been changing many times, depending on time and place. What has changed is the truth itself; what (and why) is considered true; by what means truth spreads and reproduces. So I am less interested in what the Truth is - in itself, in its essence (especially that it seems to be historically changeable) - or (making distinction) what are those different truths (modern or not; that what is currently true or considered as such). I am going to focus here on this very resolution: how Truth was (re-)constructed, how one discovers/constructs truths and what conditions they must fulfill according to given Truth. It is a two-part text, and this is first part.